Iowa foray 1977, Washington Township, Fremont County, June 3-7, annotated list of birds - Iowa State University. Special Collections and University Archives (curator); Roosa, Dean M. (contributor); Silcock, W. Ross (contributor); Stravers, Jon (contributor) (1977)
Annotated list of birds sightings seen along several routes located in Washington Township in Fremont County as well as parts of the Riverton Wildlife Management Area and the Township of Benton, June 3-7. Observers include Ross W. Silcock, Dean M. Roosa, and Jon Stravers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1977. Epson - sheet feed/flatbed